(untitled) (Albayan Scientific Journal, 2023)
This study represents an attempt to highlight the role that geomorphological phenomena can play in the Green Mountain area of Libya in military operations of all kinds, land, sea and air. The objectives of the study were to limit the most important of these phenomena that have an important role in war battles, as well as to highlight the general importance of the area geographically and strategically, in addition to trying to harness the rugged and damaged terrain to serve combat operations in the area. Two main approaches were used in the study, namely the historical and regional approach, where the study concluded that the dual role played by geomorphological phenomena according to the combat situation between the defense and attack operations, in addition to the preference for rugged and narrow terrain locations for guerrilla warfare and special forces fighting freely and ease of movement during confrontations, not to mention the use of many natural phenomena in the operations of concealment and storage of weapons, ammunition, supplies, etc., in addition to the role of the nature of the coast in the sea landing operations, and the land and sea confrontations in the area in terms of the height and the general shape of the coast and its zigzags, etc., which helps to tighten control over the balance of fighting, and to resolve the battles in favor of The forces that deal well with such phenomena have a negative and positive role at the same time, according to the type of fighting and the type of weapons used in wars of all kinds.